2017
DOI: 10.1016/j.ccl.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposures and Cardiovascular Disease

Abstract: Summary Environmental exposures in low- and middle-income countries lie at the intersection of increased economic development and the rising public health burden of cardiovascular disease. Increasing evidence suggests an association of exposure to ambient air pollution, household air pollution from biomass fuel, lead, arsenic, and cadmium with multiple cardiovascular disease outcomes including hypertension, coronary heart disease, stroke, and cardiovascular mortality. While populations in low- and middle-incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(28 citation statements)
references
References 197 publications
0
21
0
Order By: Relevance
“…In addition to respiratory diseases, there is also increasing evidence that sustained exposure to ambient and household air pollution has a particularly deleterious effect on the cardiovascular system, and an association has been found between hypertension, coronary heart disease, and stroke [ 16 ]. A 2013 review reported a pooled effect of 11% (95% CI 6 to 16%) for cardiovascular mortality with a 10 μg/m 3 PM 2.5 increase [ 43 ].…”
Section: Health Effects In Adult Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to respiratory diseases, there is also increasing evidence that sustained exposure to ambient and household air pollution has a particularly deleterious effect on the cardiovascular system, and an association has been found between hypertension, coronary heart disease, and stroke [ 16 ]. A 2013 review reported a pooled effect of 11% (95% CI 6 to 16%) for cardiovascular mortality with a 10 μg/m 3 PM 2.5 increase [ 43 ].…”
Section: Health Effects In Adult Populationmentioning
confidence: 99%
“…A 2013 review reported a pooled effect of 11% (95% CI 6 to 16%) for cardiovascular mortality with a 10 μg/m 3 PM 2.5 increase [ 43 ]. Although populations in low- and middle-income countries are highly exposed to environmental pollution, the bulk of evidence that links these exposures to cardiovascular disease is derived mostly from populations in high-income countries [ 16 ]. Pertaining to developing countries, for instance, the results of a recent study conducted by Chen and colleagues [ 44 ] clearly indicate that life-expectancy in Northern China, where air quality is particularly poor, is 5.5 years lower owing to an increased incidence of cardiorespiratory mortality.…”
Section: Health Effects In Adult Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that lead, arsenic, and cadmium exposures are linked to cardiovascular diseases and mortality (Burroughs Peña and Rollins, 2017). This area provides a newer set of disease endpoints for heavy metal exposures.…”
Section: Recent Research Discoveriesmentioning
confidence: 99%
“…Airborne particles and air pollution have long been associated with diseases and cancer (Burroughs et al , 2017). Metals are known to cause cancer via inhalation exposure (Fay et al ., 2005; Chou et al ., 2007; Wise et al ., 2008; Faroon et al ., 2012; Wilbur et al ., 2012; Wang L, et al ., 2016).…”
Section: Recent Research Discoveriesmentioning
confidence: 99%